War Experience, Daily Stressors and Mental Health Among the Inter-taliban Generation Young Adults in Northern Afghanistan: A Cross-Sectional School-Based Study - Razjouyan, Katayoon; Farokhi, Hossein; Qaderi, Farah; Qaderi, Pashtoon; Masoumi, Seyed Javad; Shah, Asghar; Pourhoseingholi, Mohamad Amin; Ahmadi, Attaullah; Lucero-Prisno, Don Eliseo III; Ozaki, Akihiko; Kotera, Yasuhiro; Shah, Jaffer; et al. (Frontiers in Psychiatry, 2022)
Background: Partial security after Taliban’s fall had led to an exponential increase in school attendance for both girls and boys in the country. As such, we decided to use schools as potential sites for intervention to address young adult’s mental health. Prior to possible interventions, a study was designed to understand the mental health state of these young adults. Methods: In a cross-sectional design, 621 high school students, were selected to participate randomly to assess war experience, daily stressors, and mental health among the first generation of young adults under post-Taliban government. Results: The participants had 17.37±0.9 mean years of ages, 94.8% of them were unmarried. Daily stressors scores were higher for female than male students (P=0.02). The majority of young adults surveyed declared themselves in agreement with statements such as the security situation in Afghanistan makes me frustrated (56%), air pollution as a concern (41 %), and not having anyone to talk about what is in their heart (28.8%). Gender differences were highly significant for mental health, as appraised by both The Hopkins Symptoms Checklist (HSCL) –depression and HSCL-anxiety. Girls present higher rates of depression, anxiety, and daily stressors than boys, and boys present higher rates of war experiences than girls. Conclusion: War experience, daily stressors, and mental health were irrelevant with age, ethnicity and marital status. Factor such as being the first-born child of the family, higher reported war experiences, and daily stressors all negatively impact mental health. Alongside war and its direct effects, the existing socio-cultural context must be considered as a potential factor mediating the mental health of girls in Afghanistan.